AB0630 Clinical spectrum time course comparison between PL-7, PL-12 and EJ positive antisynthetase syndrome. (15th June 2017) - Araguas, E Trallero; Selva, A O'Callaghan; Scire, CA; Codullo, V; Castaneda, S; Centeno, N Ortego; Silva, JA Pereira da; Fiehn, C; Schwarting, A; Manfredi, A; Emmi, G; Barsotti, S; et al.
Abstract : Background: Arthritis, myositis and Interstital lung disease (ILD) represent the classic clinical triad of antisynthetase syndrome (ASSD). In anti Jo-1 positive patients, these findings may appear also during the follow-up. Even if a similar cumulative trend has been showed also in non anti Jo-1 positive ASSD, a head to head comparison of clinical spectrum time course in these patients is still lacking Objectives: To assess the clinical spectrum time course in non anti Jo-1 positive ASSD, according to different underlying non anti Jo-1 specificities Methods: Clinical, laboratory and instrumental data collection of anti PL-7, PL-12, and EJ positive patients from an international database of ASSD Results: We identified 63 (42%) anti PL-7, 66 (44%) anti PL-12 and 20 (14%) anti EJ positive patients, reporting their characteristics in table 1 (disease onset) and 2 (last follow-up). At disease onset, no substantial differences were observed. At the end of follow-up, we observed some differences between anti PL-12 and both anti PL-7 and anti-EJ positive patients. In particular, anti PL-12 positive patients presented less frequently ex-novo triad findings and had a reduced prevalence of myositis. From the clinical point of view, the main pattern of disease presentation was an isolated ILD in all groups at the onset and only in anti-PL12 positive ASSD at last follow-up. Conclusions: Our study seems to indicate that clinical spectrum time course of anti PL-12 positive ASSD is different from that of anti PL7 and of anti EJ positive ASSD. The clinical pattern associated with these two latter antibodies was very similar. Furthermore, anti PL-12 positive patients seems to have a more stable disease, with a less common occurrence of ex-novo triad findings during the follow-up References: Cavagna L. Medicine 2015. Cavagna L. CRAI 2016. Cavagna L. ARD 2016 (Abstract). Trallero Araguas E. Scand J Rheumatol 2016. Acknowledgements: To all members of the AENEAS collaborative group. Disclosure of Interest: None declared